Development of Quizlet-Based Interactive Learning Media to Improve Student Learning Outcomes - Mediana Dwi Syafiqah; Lifa Farida Panduwinata (Economic Education Analysis Journal, 2025)
The purpose of this study is to develop an interactive learning media based on Quizlet and find out its feasibility, student response, and effectiveness in improving student learning outcomes. This research uses the Research and Development (R&D) method with the ADDIE model. The sample of this study came from two classes with a total sample of 63 students with details of the control class of 34 students and 29 students in the experimental class. The effectiveness of the learning media was measured using the N-Gain analysis test from the experimental class and the control class. The research instruments consist of material validation sheets and media experts, student response questionnaires and evaluation questions. The data was analyzed descriptively quantitatively. The results of the study showed that the learning media developed met the eligibility criteria of 83% of material experts in the "very feasible" category and 76% of media experts in the "feasible" category and received a positive response from students of 83.67%. Based on the results of the N-Gain test, 69% of the results were obtained with the interpretation of "quite effective" in improving learning outcomes and can be used in the learning process.